Thyroid Cancer After Chernobyl: Re-Evaluation Needed - Sergei JARGIN (Federation of Turkish Pathology Societies, 2021)
Thyroid carcinoma in people exposed to radiation during their childhood and adolescence is the only solid cancer for which the incidence increase as a result of the Chernobyl accident is regarded to be proven. The main evidence in favor of a cause-effect relationship between radiation and thyroid cancer incidence increase comes from epidemiologic studies. Bias in some studies was caused by the screening effect, improved diagnostics after the accident, overdiagnosis, registration of patients from non-contaminated territories as Chernobyl victims, recall bias, dose-dependent selection and self-selection. Prior to the accident, the registered incidence of pediatric thyroid carcinoma was lower in the former Soviet Union than in other industrialized countries i.e. there were undiagnosed cases in the population. The screening found not only small nodules but also late-stage tumors interpreted as radiogenic cancers developing after a short latency. Pediatric thyroid cancers detected during first 10 years after the accident were larger than those detected later on average, many tumors being poorly differentiated and metastatic. The relationship of thyroid cancer and Chernobyl exposures is not denied here; however, it is argued that the quantity of radiogenic cases has been overestimated according to the mechanisms discussed in this paper. In addition, it is suggested that results of some Chernobyl-related molecular-genetic and other studies should be re-evaluated, considering that many tumors detected by the screening or brought from non-contaminated areas and registered as exposed to the fallout were advanced cancers.